Odpowiedź :
3.
a) 3x + 7 = 2x + 1
3x - 2x = 1 - 7
x = -6
b) x = 8 - 3x
x + 3x = 8
4x = 8 /:4
x = 2
c) 2x - 4 = 4x - 2
2x - 4x = -2 + 4
-2x = 2 /:(-2)
x = -1
d) 7 - 2x = 5x = 28
-2x - 5x = 28 -7
-7x = 21 /:(-7)
x = -3
e) 8x - 5 = 9x - 5
8x - 9x = -5 + 5
x = 0
f) 6x + 2x - 10 = 3x + 5
6x + 2x - 3x = 5 + 10
5x = 15 /:5
x = 3
g) x + 2x + 3x = 5 + 6 + 7
6x = 18 /:6
x = 3
h) 4x - 1 + 5x = 6x + 1 - 7x
4x + 5x - 6x + 7x = 1 + 1
10x = 2 /:10
x = [tex]\frac{1}{5}[/tex]
i) 0 = 4x - 4 + 5x - 5
4 + 5 = 4x + 5x
9 = 9x /:9
x = 1
4.
a) 2(3 - x) + 7 = 4x - 5(2 + x)
6 - 2x + 7 = 4x - 10 - 5x
13 - 2x = -x - 10
13 + 10 = -x + 2x
23 = x
Spr. 2(3 - 23) + 7 = 4*23 - 5(2 + 23)
2 * (-20) + 7 = 92 - 125
-33 = -33
L = P
b) -17x + 4(x - 7) = -3(3x - 1) + 1
-17x + 4x - 28 = -9x + 3 + 1
-13x - 28 = -9x + 4
-13x + 9x = 4 + 28
-4x = 32 /:(-4)
x = -8
Spr. -17*(-8) + 4(-8 - 7) = -3(3* (-8) - 1) + 1
136 - 60 = -3 * (-25) + 1
76 = 75 + 1
76 = 76
L = P
c) 2(x + 4) - 1 = 5x + 2
2x + 8 - 1 = 5x + 2
2x - 5x = 2 - 7
-3x = -5 /-3
x = [tex]\frac{5}{3}[/tex]
Spr. 2([tex]\frac{5}{3}[/tex] + 4) - 1 = 5* [tex]\frac{5}{3}[/tex] + 2
2 * [tex]\frac{17}{3}[/tex] - 1 = [tex]\frac{25}{3}[/tex] + 2
[tex]\frac{31}{3}[/tex] = [tex]\frac{31}{3}[/tex]
P = L
d) [tex]\frac{x-1}{2}[/tex] = x + 1 /*2
x - 1 = 2x + 2
x - 2x = 2 + 1
-x = 3 /:(-1)
x = -3
Spr. [tex]\frac{-3-1}{2}[/tex] = -3 + 1 /*2
-3 -1 = -6 + 2
-4 = -4
L = P
5. Odp. B